Uma investigação sobre a solução de problemas a partir da experiência do CCQ: análise da teoria e da prática - Fernando Antonio Lomelino Campos (2004)
This dissertation investigates the solution of problems starting from the Quality Control Circles - QCC with comprehensive theory and practice. It starts from the philosophy developed in Japan, analyzing diverse theories about Solution of problems and finally, focus on the analysis of the practice of Brazilian Quality Control Circles, by means of records and interviews direct to the circle participants and coordinators. In comparison with the original philosophy, the Brazilian experience presents bias,although it certifies that such philosophy (which is representative of human beings universal desire) is latent as a profound desire in all circles analyzed. In some circles the philosophy is explicitly experienced.In relation to the Solution of Problems Method, it is explicit a possible confusion between a pure scientific approach, not applicable in day-by-day basis, and a pragmatic approach as a proposal to the Quality Control Circles. It certifies that even in the pragmatic approach ofQuality Control Circles, may occur dogmatism which prevents the accomplishment of the human capacity to create wealth. This discourage the participants of the Quality Control Circles. On the other hand, it is verified some outlets that permits a return to a more realistic approach to the way to act of the human being when solving problems. On the perspective of the Quality Control Circles in progress, it is verified thetransforming effect even when it is taken into consideration the misinterpretation by the companies. The level of enthusiasm at the conventions, taken into consideration that QCC was almost extinct in Brazil, demonstrates that the proposal made by Kaoru Ishikawa is based on a universal perspective of human nature. Thus, the return of the Quality Control Circles in Brazil in 1990s demonstrates that it is a social movement of a high impact so as to form the citizen and the worker of the knowledge era. The research concludes positively for the acceptance of the Quality Control Circles as a source of reference to enable citizens and workers to act as scientists, engineers and managers in action regardless his formal educational level. The movement if adopted in an integrated management perspective can, as the author believes,represent a factor of advance to the social development of the country.